Repercussões de um curso de formação continuada à distância na constituição da identidade profissional de um grupo de professores do ensino fundamental no Maranhão - Oliveira Filho, Vicente Henrique de (2016)
This qualitative research aimed to understand the repercussions of participation at "Pro-Literacy Mathematics’ Program" in the professional identity in a group of 18 teachers from the early years of elementary school in Maranhão’s state.To collect data, they were used questionnaires, semi-structured interviews, documents related to the course and memorials built by the teachers during the formation. It was applied Discursive Textual Analysis (MORAES; GALIAZZI, 2011) to analyze the data, established in four stages. The first one was text’s organization (corpus) that emerged from the collected data. After that, it was consituted unitarization of meaning elements to the research and extracted from the corpus. After analyzing the unitarization and grouping them by common ideas four categories emerged: (1) Teachers’ perceptions on mathematical knowledge and the child's learning; (2) Teacher's Pedagogical work and his inclusion at the student's context; (3) Pro-Literacy course as improvement of pedagogical practice; and (4) Personal experiences and formation of professional teaching identity. From the outlined categories were developed metatexts with the discussion of the results obtained in the research. It is noticed that continuing education is considered by teachers as an incentive to upgrade to the use of pedagogical practices closer to the reality of students. Teachers declare that is needed to teachers and students recognize the process of teaching and learning mathematics as something practical and reflective. It is noticed that the student's motivation also motivates the teacher. The course presentation strategy, with periodic face meetings, is well assimilated by the participants, as it enables the interaction between course participants. Life experiences and the profession are supported to form their identity. It was concluded that continuing education is a very positive opportunity to the teacher to review various aspects related to the exercise of their activities and contribute to establish their professional identity.